Manufacturing method of electrolytic capacitor

The described method enhances electrolytic capacitors' conductivity and heat resistance by using chemical oxidative polymerization with ferric aromatic sulfonate and aromatic sulfonic acids, addressing the limitations of previous technologies in achieving low ESR and high heat resistance.

JP2025007944APending Publication Date: 2025-01-17TAYCA CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023109717
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-04
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing electrolytic capacitors face challenges in achieving low equivalent series resistance (ESR) while maintaining excellent heat resistance, as previous methods have not adequately addressed these properties simultaneously.

Method used

A manufacturing method for electrolytic capacitors involves forming a conductive polymer layer using chemical oxidative polymerization of thiophene derivatives with ferric aromatic sulfonate as an oxidizing agent and dopant, incorporating organic acids or salts with aromatic rings, and performing a pretreatment step with a solution containing aromatic sulfonic acids or their salts to enhance conductivity and heat resistance.

Benefits of technology

The method results in electrolytic capacitors with significantly reduced ESR and improved heat resistance, maintaining performance under high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007944000001
    Figure 2025007944000001
  • Figure 2025007944000002
    Figure 2025007944000002
  • Figure 2025007944000003
    Figure 2025007944000003
Patent Text Reader

Abstract

To provide a manufacturing method of an electrolytic capacitor, having a low ESR and an excellent heat resistance.SOLUTION: A manufacturing method of an electrolytic capacitor of the present invention, includes: a step of forming an internal layer of a conductive polymer by polymerizing thiophene or their inductor to a chemical oxidation as a step of forming the conductive polymer onto an inductor layer of a capacitor element; and a step of forming an outer layer of the conductive polymer by polymerizing thiophene or their inductor to the chemical oxidation after a pre-processing liquid is coated to the capacitor element into which the inner layer is formed, and a pre-processing for drying them is excited. As a pre-processing liquid, an organic acid containing an aromatic ring or salt other than a transition metal is contained at a concentration of 10 to 50 mass%, and a solution containing an aromatic sulfonic acid or at least salt other than the transition metal as an organic acid or their salt is used.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an electrolytic capacitor having a low ESR and excellent heat resistance. [Background technology]

[0002] Due to their high electrical conductivity, conductive polymers are used as electrolytes (solid electrolytes) in, for example, aluminum electrolytic capacitors, tantalum electrolytic capacitors, niobium electrolytic capacitors, and the like.

[0003] As the conductive polymer for this application, for example, one obtained by chemical oxidative polymerization or electrolytic oxidative polymerization of thiophene or its derivatives is used.

[0004] In addition, various studies have been conducted to improve the characteristics of electrolytic capacitors. For example, Patent Document 1 proposes a technique for improving the conductivity, heat resistance, moisture resistance, etc. of electrolytic capacitors by coating them with an organic sulfonate consisting of an anion of an organic sulfonic acid and a cation other than a transition metal, or by using a conductive polymer containing the organic sulfonate as a solid electrolyte.

[0005] Furthermore, Patent Document 2 discloses that a capacitor element is treated with a pretreatment liquid containing a compound having an aromatic ring, either a benzene ring or a naphthalene ring, at least one carboxyl group, and either having or not having a hydroxyl group bonded to a constituent carbon of the aromatic ring, and having a total of two or more carboxyl groups and / or hydroxyl groups, and an organic solvent having a boiling point of less than 150°C, and a solid electrolyte layer is formed on the capacitor element using a conductive polymer obtained by chemically oxidatively polymerizing thiophene or a derivative thereof, and an electrolytic capacitor is constructed using the solid electrolyte layer, thereby improving the heat resistance of the capacitor. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2005 / 014692 [Patent Document 2] JP 2020-178107 A Summary of the Invention [Problem to be solved by the invention]

[0007] The techniques described in Patent Documents 1 and 2 are both effective in increasing the heat resistance of electrolytic capacitors, but it is difficult to obtain electrolytic capacitors with low ESR (equivalent series resistance), and there is still room for improvement in this regard.

[0008] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a method for manufacturing an electrolytic capacitor having a low ESR and excellent heat resistance. [Means for solving the problem]

[0009] The method for producing an electrolytic capacitor of the present invention is a method for producing an electrolytic capacitor including a capacitor element having a dielectric layer formed on a metal porous body, the capacitor element having a conductive polymer layer on the dielectric layer, and the step of forming the conductive polymer layer includes an inner layer forming step of performing an operation of chemically oxidizing and polymerizing thiophene or a derivative thereof on a surface of the dielectric layer at least once using aromatic ferric sulfonate as an oxidant and dopant to form an inner layer of the conductive polymer layer, and a pretreatment step of applying a pretreatment liquid to the capacitor element on which the conductive polymer layer has been formed and drying the pretreated capacitor element, and performing an operation of chemically oxidizing and polymerizing thiophene or a derivative thereof on the pretreated capacitor element at least once using aromatic ferric sulfonate as an oxidant and dopant to form an outer layer of the conductive polymer layer on the inner layer, the pretreatment liquid being characterized in that a solution containing an aromatic ring-containing organic acid or a salt other than a transition metal salt thereof at a concentration of 10 to 50 mass % is used as the organic acid or a salt thereof, and the organic acid or salt thereof contains at least an aromatic sulfonic acid or a salt other than a transition metal salt thereof. Effect of the Invention

[0010] According to the present invention, a method for producing an electrolytic capacitor having low ESR and excellent heat resistance can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The manufacturing method of the present invention includes, as a step of forming a conductive polymer layer on a dielectric layer of a capacitor element, an inner layer forming step of forming an inner layer (hereinafter, sometimes simply referred to as "inner layer") of the conductive polymer layer, and an outer layer forming step of forming an outer layer (hereinafter, sometimes simply referred to as "outer layer") of the conductive polymer layer on the inner layer after performing a pretreatment with a specific pretreatment liquid. In the pretreatment performed prior to chemical oxidative polymerization in the outer layer forming step, a solution containing an aromatic ring-containing organic acid or a salt other than a transition metal salt thereof at a concentration of 10 to 50 mass % and containing at least an aromatic sulfonic acid or a salt other than a transition metal salt thereof as the organic acid or the salt thereof is used as the pretreatment liquid. The conductive polymer layer functions as a solid electrolyte layer of an electrolytic capacitor.

[0012] In the manufacturing method of the present invention, in the inner layer forming step and the outer layer forming step, thiophene or its derivative is chemically oxidatively polymerized in the coexistence of aromatic ferric sulfonate to form a conductive polymer. The aromatic ferric sulfonate functions as an oxidizing agent during the chemical oxidative polymerization to promote the polymerization of thiophene or its derivative, and its anion is incorporated into the synthesized conductive polymer, where the anion functions as a dopant to improve the conductivity of the conductive polymer.

[0013] Here, the organic acid containing an aromatic ring or the salt other than a transition metal salt thereof, such as the aromatic sulfonic acid or the salt other than a transition metal salt thereof, contained in the pretreatment liquid also functions as an oxidizing agent and dopant when forming the outer layer of the conductive polymer. Since the pretreatment liquid contains the organic acid containing an aromatic ring or the salt other than a transition metal salt thereof at a high concentration, the formation of the outer layer of the conductive polymer is further promoted by the function as an oxidizing agent, and the organic acid containing an aromatic ring or the salt other than a transition metal salt thereof is incorporated in a large amount in the conductive polymer layer after formation.

[0014] An electrolytic capacitor having a conductive polymer layer incorporating a large amount of an organic acid containing an aromatic ring or a salt other than a transition metal salt thereof as a solid electrolyte layer has a low ESR. In addition, an organic acid containing an aromatic ring or a salt other than a transition metal salt thereof also has the effect of increasing the heat resistance of a conductive polymer, so that the heat resistance of an electrolytic capacitor is improved by using a conductive polymer layer containing a large amount of the organic acid as a solid electrolyte layer. Among the organic acids containing an aromatic ring or salts other than a transition metal salt thereof, aromatic sulfonic acids or salts other than a transition metal salt thereof are excellent in reducing the ESR of an electrolytic capacitor and increasing the heat resistance of an electrolytic capacitor, and in the manufacturing method of the present invention, by including the aromatic sulfonic acid in the pretreatment solution used before chemical oxidation polymerization in the outer layer forming process of the conductive polymer, it is possible to provide an electrolytic capacitor with a low ESR and excellent heat resistance.

[0015] The production method of the present invention will be described in detail below.

[0016] <Inner layer formation process> In the inner layer forming step, an inner layer made of a conductive polymer is formed on the dielectric layer of the capacitor element.

[0017] The manufacturing method of the present invention uses a capacitor element having a dielectric layer formed on a metallic porous body. The metallic porous body constituting the capacitor element includes a porous body of a valve metal such as aluminum, tantalum, or niobium.

[0018] The dielectric layer in the capacitor element can be formed by oxidizing the metal on the surface of a metallic porous body, for example by subjecting the porous body to a chemical conversion treatment.

[0019] The formation of the conductive polymer inner layer on the dielectric layer of the capacitor element is carried out by chemically oxidizing and polymerizing thiophene or its derivatives using aromatic ferric sulfonate as an oxidizing agent and dopant.

[0020] Examples of thiophene derivatives among thiophene or derivatives thereof used as a monomer for a conductive polymer include 3,4-ethylenedioxythiophene (EDOT), 3-alkylthiophene, 3-alkoxythiophene, 3-alkyl-4-alkoxythiophene, 3,4-alkylthiophene, 3,4-alkoxythiophene, and alkylated ethylenedioxythiophene (alkylated EDOT) obtained by modifying the above-mentioned 3,4-ethylenedioxythiophene with an alkyl group. The number of carbon atoms in the alkyl group or alkoxy group is preferably 1 or more and is preferably 16 or less, more preferably 10 or less, and even more preferably 4 or less.

[0021] To explain in detail about alkylated EDOT, which is the above-mentioned EDOT modified with an alkyl group, EDOT and alkylated EDOT correspond to the compounds represented by the following general formula (1).

[0022] General formula (1): [ka]

[0023] In general formula (1), R 1 is hydrogen or an alkyl group having 1 to 10 carbon atoms.

[0024] And, R in the above general formula (1) 1The compound where R is hydrogen is EDOT, and its IUPAC name is "2,3-Dihydro-thieno[3,4-b][1,4]dioxine". However, this compound is more often represented by its general name "3,4-ethylenedioxythiophene" than by its IUPAC name, so in this specification, this "2,3-Dihydro-thieno[3,4-b][1,4]dioxine" is represented as "3,4-ethylenedioxythiophene (EDOT)". And, R in the above general formula (1) 1 When R is an alkyl group, the alkyl group preferably has 1 to 10 carbon atoms, and more preferably has 1 to 4 carbon atoms. That is, the alkyl group is particularly preferably a methyl group, an ethyl group, a propyl group, or a butyl group. Specific examples of these include R in the general formula (1). 1 The compound where R is a methyl group is called "2-Methyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine" in IUPAC name, but in the following of this specification, this will be abbreviated to "methylated ethylenedioxythiophene (methylated EDOT)". 1 The IUPAC name for the compound with an ethyl group is "2-Ethyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine," but in this specification, this is abbreviated to "ethylated ethylenedioxythiophene (ethylated EDOT)."

[0025] R in general formula (1) 1The compound with a propyl group is called "2-propyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine" in IUPAC name, but in this specification, this is abbreviated to "propylated ethylenedioxythiophene (propylated EDOT)". 1 The compound with a butyl group is called 2-butyl-2,3-dihydro-thieno[3,4-b][1,4]dioxin in IUPAC name. In this specification, the term "2-alkyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine" is abbreviated to "butylated ethylenedioxythiophene (butylated EDOT)". In addition, in this specification, "2-alkyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine" is abbreviated to "alkylated ethylenedioxythiophene (alkylated EDOT)". Among these alkylated EDOTs, methylated EDOT, ethylated EDOT, propylated EDOT, and butylated EDOT are preferred.

[0026] It is preferable to use a mixture of EDOT (i.e., 2,3-dihydro-thieno[3,4-b][1,4]dioxine) and alkylated EDOT (i.e., 2-alkyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine), with the mixing ratio being preferably 0.05:1 to 1:0.1, more preferably 0.1:1 to 1:0.1, even more preferably 0.2:1 to 1:0.2, and particularly preferably 0.3:1 to 1:0.3, in terms of molar ratio.

[0027] In the synthesis of the conductive polymer, ferric aromatic sulfonate is used as an oxidizing agent and dopant. Specific examples of ferric aromatic sulfonate that can be used as an oxidizing agent and dopant include ferric salts of aromatic sulfonic acids such as paratoluenesulfonic acid, benzenesulfonic acid or its derivatives, naphthalenesulfonic acid or its derivatives, and anthraquinonesulfonic acid or its derivatives, and one or more of these can be used. Among these aromatic ferric sulfonates, it is preferable to use ferric paratoluenesulfonate or ferric naphthalenesulfonate.

[0028] The ferric aromatic sulfonate preferably has a molar ratio of aromatic sulfonic acid to iron of less than 1:3. This is because by reducing the molar ratio of aromatic sulfonic acid to iron below the stoichiometric molar ratio of 1:3, the reaction rate of the ferric aromatic sulfonate can be slightly reduced, and the molar ratio of aromatic sulfonic acid to iron is preferably up to about 1:2, more preferably up to about 1:2.2, particularly preferably up to about 1:2.4, and even more preferably up to about 1:2.75.

[0029] The oxidant-cum-dopant can be used in the form of an organic solvent solution (oxidant-cum-dopant solution) for forming the inner layer. Examples of the solvent for the oxidant-cum-dopant solution include monohydric lower alcohols having a hydrocarbon group with 1 to 4 carbon atoms, such as methanol, ethanol, propanol, butanol, and polyhydric alcohols, such as ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, and polyethylene glycol, and among these, monohydric lower alcohols, such as methanol, ethanol, propanol, and butanol, are more preferred.

[0030] The concentration of the aromatic ferric sulfonate in the oxidant / dopant solution is usually 30 to 70 mass %.

[0031] The inner layer can be formed by synthesizing a conductive polymer on the capacitor element by chemical oxidative polymerization using the following method: (a) immersing the capacitor element in a monomer (thiophene or its derivative) or in a monomer solution obtained by diluting the monomer with a solvent, lifting it up and drying it, then immersing the capacitor element in an oxidant / dopant solution containing ferric aromatic sulfonate, and then chemically oxidizing the monomer after lifting it up; (b) immersing the capacitor element in an oxidant / dopant solution, lifting it up and drying it, then immersing the capacitor element in a monomer or in a monomer solution, and then chemically oxidizing the monomer after lifting it up; (c) immersing the capacitor element in a polymerization solution prepared by adding a monomer to an oxidant / dopant solution, then chemically oxidizing the monomer after lifting it up; or the like. The chemical oxidative polymerization is carried out, for example, at 5 to 95° C. for 1 to 72 hours. After the chemical oxidative polymerization, the capacitor element is usually washed and dried.

[0032] In the chemical oxidative polymerization of the monomer, the molar ratio of the aromatic ferric sulfonate to the monomer is preferably ferric aromatic sulfonate:monomer=2:1 to 15:1.

[0033] Thiophene or its derivatives as monomers are liquid at room temperature, so they can be used as they are in polymerization, but in order to make the polymerization reaction proceed more smoothly, they may be used as a monomer solution in which water or a lower alcohol is used as a solvent. Examples of lower alcohols include alcohols having 1 to 4 carbon atoms, such as methanol, ethanol, propanol, and butanol. As the solvent for the monomer solution, only one of the various solvents exemplified above may be used, or two or more of them may be used. The concentration of thiophene or its derivatives in the monomer solution is preferably, for example, 10 to 80 mass%.

[0034] In forming the inner layer, the chemical oxidative polymerization (as well as the series of operations up to washing and drying) may be carried out only once. However, from the viewpoint of better suppressing the deterioration of the characteristics of the electrolytic capacitor due to the components of the pretreatment liquid described below, it is preferable to repeat the process two or more times to make the inner layer thicker. Specifically, the number of repetitions is usually about 2 to 10 times.

[0035] <Outer layer formation process> In the outer layer forming step, first, a pretreatment liquid is applied to the capacitor element on which the inner layer has been formed, and the pretreatment liquid is dried.

[0036] The pretreatment liquid contains an aromatic ring-containing organic acid or a salt thereof other than a transition metal salt thereof, and contains, as the organic acid or a salt thereof, at least an aromatic sulfonic acid or a salt thereof other than a transition metal salt thereof.

[0037] In addition, if an aromatic ring-containing organic acid or a salt thereof other than a transition metal salt is directly attached to the metal porous body or dielectric layer of the capacitor element, the characteristics of the electrolytic capacitor using the same may be deteriorated. Therefore, the pretreatment using the pretreatment liquid is carried out after the inner layer is formed on the dielectric layer of the capacitor element by the inner layer forming step.

[0038] Examples of aromatic sulfonic acids and aromatic sulfonic acids that form salts other than transition metal salts of aromatic sulfonic acids include those having an anthracene skeleton (anthraquinone sulfonic acid, anthraquinone disulfonic acid, anthraquinone trisulfonic acid), those having a naphthalene skeleton (naphthalenesulfonic acid, naphthalene disulfonic acid, naphthalene trisulfonic acid, etc.), and those having a benzene skeleton and containing a carboxyl group (sulfosalicylic acid, etc.).

[0039] In addition, examples of salts other than the transition metal salts of aromatic sulfonic acids include salts having cations of metals other than transition metals and organic cations as cations. Examples of cations of metals other than transition metals include sodium ions, potassium ions, magnesium ions, calcium ions, and aluminum ions. Examples of organic cations include cationized basic organic substances such as ethanolamine, diethanolamine, isopropanolamine, diisopropanolamine, triisopropanolamine, 1,2-propanediamine, 1,3-propanediamine, aminoanthraquinone, aminoazotoluene, naphthylamine, adenine, and 1-methylimidazole. Among these, salts of organic sulfonic acids having diethanolamine, triisopropanolamine, and 1-methylimidazole as cations can increase the concentration of the pretreatment solution and can improve the heat resistance of the electrolytic capacitor, so these organic cations are preferable as cations of salts other than the transition metal salts of aromatic sulfonic acids.

[0040] The pretreatment liquid may contain only one of the above-exemplified salts as the aromatic sulfonic acid or its salt other than the transition metal salt, or may contain two or more of them.

[0041] In addition, it is preferable that the pretreatment liquid contains, as an aromatic ring-containing organic acid or a salt thereof other than a transition metal salt, an aromatic carboxylic acid or a salt thereof other than a transition metal salt, together with an aromatic sulfonic acid or a salt thereof other than a transition metal salt. In this case, it is possible to further improve the heat resistance of the electrolytic capacitor.

[0042] Incidentally, among organic acids having an aromatic ring, there are those having both a sulfonic acid group and a carboxyl group, such as sulfosalicylic acid. In this specification, however, those having a sulfonic acid group are considered to be aromatic sulfonic acids even if they also have a carboxyl group.

[0043] Examples of aromatic carboxylic acids and aromatic carboxylic acids that form salts other than transition metal salts of aromatic carboxylic acids include benzenedicarboxylic acids (phthalic acid, isophthalic acid, terephthalic acid), benzenetricarboxylic acid, benzenetetracarboxylic acid, hydroxybenzenecarboxylic acid (hydroxybenzoic acid), dihydroxybenzenecarboxylic acid, trihydroxybenzenecarboxylic acid, hydroxybenzenedicarboxylic acid, dihydroxybenzenedicarboxylic acid, aminohydroxybenzenecarboxylic acid, hydroxytoluenecarboxylic acid, aminohydroxybenzenecarboxylic acid, hydroxytoluenecarboxylic acid, hydroxynitrobenzenecarboxylic acid (hydroxynitrobenzoic acid), dihydroxynitrobenzenecarboxylic acid (dihydroxynitrobenzoic acid), nitrobenzenedicarboxylic acid, and dinitrobenzenedicarboxylic acid, and other carboxylic acids having a benzene skeleton; hydroxynaphthalenecarboxylic acid (hydroxynaphthoic acid), dihydroxynaphthalenecarboxylic acid, trihydroxynaphthalenecarboxylic acid, hydroxynaphthalene dicarboxylic acid, dihydroxynaphthalene dicarboxylic acid, and other carboxylic acids having a naphthalene skeleton, such as acetylaminohydroxynaphthalenecarboxylic acid.

[0044] In addition, examples of salts other than the transition metal salts of aromatic carboxylic acids include salts having cations of metals other than transition metals and organic cations. Examples of cations of metals other than transition metals include the same metal cations as those exemplified above for salts other than the transition metal salts of aromatic sulfonic acids. Examples of organic cations include the same organic cations as those exemplified above for salts other than the transition metal salts of aromatic sulfonic acids. Among these, salts of organic sulfonic acids having diethanolamine, triisopropanolamine, and 1-methylimidazole as cations can increase the concentration of the pretreatment liquid and can improve the heat resistance of the electrolytic capacitor, so these organic cations are preferred as cations of salts other than the transition metal salts of aromatic carboxylic acids.

[0045] When the pretreatment liquid contains a salt other than an aromatic carboxylic acid or a transition metal salt thereof, it may contain only one kind of the above-mentioned examples, or may contain two or more kinds.

[0046] The solvent for the pretreatment liquid may be a monohydric lower alcohol having a hydrocarbon group having 1 to 4 carbon atoms, such as methanol, ethanol, propanol, or butanol; a polyhydric alcohol, such as ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, or polyethylene glycol; or water; and among these, a monohydric lower alcohol, such as methanol, ethanol, propanol, or butanol, or water is more preferred.

[0047] The concentration of the organic acid containing an aromatic ring or a salt other than a transition metal salt thereof in the pretreatment liquid (when the pretreatment liquid contains a plurality of organic acids containing an aromatic ring or a salt other than a transition metal salt thereof, the total concentration thereof; the same applies below) is 10% by mass or more, and preferably 20% by mass or more, from the viewpoint of reducing the ESR of the electrolytic capacitor and enhancing the heat resistance. However, if the amount of the organic acid containing an aromatic ring or a salt other than a transition metal salt thereof in the pretreatment liquid is too large, the initial characteristics of the electrolytic capacitor tend to deteriorate, so the concentration of the organic acid containing an aromatic ring or a salt other than a transition metal salt thereof in the pretreatment liquid is 50% by mass or less, and preferably 40% by mass or less.

[0048] The pretreatment liquid may contain only an aromatic sulfonic acid or a transition metal salt thereof as a salt other than an aromatic ring-containing organic acid or a transition metal salt thereof. Therefore, the concentration of the aromatic sulfonic acid or the transition metal salt thereof in the pretreatment liquid is preferably 10 mass % or more, more preferably 20 mass % or more, and is preferably 50 mass % or less, and more preferably 40 mass % or less.

[0049] Furthermore, when the pretreatment liquid contains a salt other than an aromatic carboxylic acid or a transition metal salt thereof, the concentration of the aromatic carboxylic acid or the salt other than a transition metal salt thereof in the pretreatment liquid is preferably 5 to 30 mass %, from the viewpoint of better ensuring the effects of its use.

[0050] Methods for applying the pretreatment liquid to a capacitor element having an inner layer formed thereon include a method of immersing the capacitor element in a bath filled with the pretreatment liquid and then pulling it out, and a method of spraying the pretreatment liquid onto the capacitor element.

[0051] After the pretreatment liquid is applied to the capacitor element, the pretreatment liquid is dried. There are no particular limitations on the drying method as long as the method does not decompose the components (aromatic ring-containing organic acid or its salt other than a transition metal salt) contained in the pretreatment liquid applied to the capacitor element, and various known drying methods (air drying, hot air drying, etc.) can be used.

[0052] A conductive polymer outer layer is formed on the inner layer of the pretreated capacitor element. The conductive polymer outer layer is formed by chemically oxidizing and polymerizing thiophene or its derivatives using aromatic ferric sulfonate as an oxidant and dopant. The same aromatic ferric sulfonate and monomer (thiophene or its derivative) as exemplified above in the inner layer formation method can be used for the chemical oxidizing and polymerizing to form the outer layer, and the same method and conditions as those described in the inner layer formation method (c) can be used to prepare a polymerization solution by adding a monomer to an oxidant and dopant solution, in which the capacitor element is immersed in the polymerization solution, and then pulled out and the monomer is chemically oxidized and polymerized.

[0053] The inner layer forming step and the outer layer forming step may use the same or different monomers. Furthermore, the inner layer forming step and the outer layer forming step may use the same oxidizer / dopant (ferric aromatic sulfonate) or different oxidizer / dopants.

[0054] After the chemical oxidative polymerization, washing and drying are usually carried out in the same manner as in the case of the inner layer forming step.

[0055] In forming the outer layer, the chemical oxidative polymerization (as well as a series of operations up to washing and drying) may be carried out only once, but may be repeated multiple times to cover the entire capacitor element. Specifically, the number of repetitions is usually about 1 to 3 times.

[0056] The conductive polymer layer formed on the dielectric layer of the capacitor element through the inner layer forming step and the outer layer forming step has a thickness of, for example, 1 to 20 μm.

[0057] The thickness of the inner layer is preferably 0.1 μm or more from the viewpoint of better suppressing deterioration of the properties of the electrolytic capacitor due to the components of the pretreatment liquid. Furthermore, the thickness of the outer layer is preferably 5 μm or more from the viewpoint of better ensuring the effect of reducing the ESR and the effect of improving the heat resistance of the electrolytic capacitor. The upper limit of the thickness of the inner layer and the upper limit of the thickness of the outer layer are determined within a range in which the thickness of the conductive polymer layer satisfies the above-mentioned preferred value.

[0058] Alternatively, a conductive polymer layer may be formed on the capacitor element by chemical oxidative polymerization, and then a layer may be formed on the conductive polymer layer using a dispersion of a π-conjugated conductive polymer.

[0059] The π-conjugated conductive polymer is a π-conjugated conductive polymer using a polymer anion as a dopant. The polymer anion is mainly composed of polymeric sulfonic acid, and specific examples thereof include polystyrene sulfonic acid, sulfonated polyester, phenolsulfonic acid novolac resin, and copolymers of styrene sulfonic acid and non-sulfonic acid monomers (methacrylic acid esters, acrylic acid esters, and unsaturated hydrocarbon-containing alkoxysilane compounds or their hydrolysates).

[0060] After the conductive polymer layer is formed on the capacitor element as described above, for example, carbon paste or silver paste is applied, dried, and then an exterior is applied to complete an electrolytic capacitor.

[0061] Since the electrolytic capacitor of the present invention has a low ESR and excellent heat resistance, it can be suitably used in applications requiring such characteristics, and can also be used in the same applications in which electrolytic capacitors have been used conventionally. EXAMPLES

[0062] The present invention will be described in detail below with reference to examples, although the present invention is not limited to the following examples.

[0063] (Preparation of ethanol solution for pretreatment) Preparation Example 1 Naphthalenesulfonic acid was dissolved in ethanol to a concentration of 10% by mass to prepare an ethanol solution of naphthalenesulfonic acid.

[0064] Preparation Example 2 Naphthalenesulfonic acid was dissolved in ethanol at a concentration of 30% by mass to prepare an ethanol solution of naphthalenesulfonic acid.

[0065] Preparation Example 3 Naphthalenesulfonic acid was dissolved in ethanol at a concentration of 50% by mass to prepare an ethanol solution of naphthalenesulfonic acid.

[0066] Preparation Example 4 Naphthalenedisulfonic acid was dissolved in ethanol at a concentration of 30% by mass to prepare an ethanol solution of naphthalenedisulfonic acid.

[0067] Preparation Example 5 Naphthalene trisulfonic acid was dissolved in ethanol at a concentration of 30 mass % to prepare an ethanol solution of naphthalene trisulfonic acid.

[0068] Preparation Example 6 15 g of diethanolamine was added to an aqueous solution prepared by dissolving 30 g of naphthalenesulfonic acid in 70 ml of water, and the solvent was then replaced with ethanol to prepare an ethanol solution containing a salt of naphthalenesulfonic acid and diethanolamine at a concentration of 30% by mass.

[0069] Preparation Example 7 An ethanol solution containing a salt of naphthalenesulfonic acid and triisopropanolamine at a concentration of 30% by mass was prepared in the same manner as in Preparation Example 6, except that 28 g of triisopropanolamine was used instead of diethanolamine.

[0070] Preparation Example 8 An ethanol solution containing a salt of naphthalenesulfonic acid and 1-methylimidazole at a concentration of 30% by mass was prepared in the same manner as in Preparation Example 6, except that 12 g of 1-methylimidazole was used instead of diethanolamine.

[0071] Preparation Example 9 Sulfosalicylic acid was dissolved in ethanol at a concentration of 30% by mass to prepare an ethanol solution of sulfosalicylic acid.

[0072] Preparation Example 10 Hydroxybenzoic acid was dissolved in ethanol at a concentration of 30% by mass to prepare an ethanol solution of hydroxybenzoic acid.

[0073] Preparation Example 11 15 g of diethanolamine was added to an aqueous solution prepared by dissolving 20 g of hydroxybenzoic acid in 80 ml of water, and the solvent was then replaced with ethanol to prepare an ethanol solution containing a salt of hydroxybenzoic acid and diethanolamine at a concentration of 30% by mass.

[0074] Preparation Example 12 Phthalic acid was dissolved in ethanol at a concentration of 30% by mass to prepare an ethanol solution of phthalic acid.

[0075] Preparation Example 13 Naphthalenesulfonic acid was dissolved in ethanol to a concentration of 5% by mass to prepare an ethanol solution of naphthalenesulfonic acid.

[0076] Preparation Example 14 Naphthalenesulfonic acid was dissolved in ethanol at a concentration of 60% by mass to prepare an ethanol solution of naphthalenesulfonic acid.

[0077] The compositions of the ethanol solutions prepared in Preparation Examples 1 to 14 are shown in Table 1.

[0078] [Table 1]

[0079] Example 1 (Formation of the inner layer) An oxidant and dopant solution was prepared by mixing ferric paratoluenesulfonate in an amount to give a concentration of 40 mass % with ethanol.

[0080] A rectangular tantalum sintered compact (one end of a lead wire is embedded in the tantalum sintered compact, and the other end protrudes from one surface of the tantalum sintered compact) was immersed in a 2 mass% phosphoric acid aqueous solution and a voltage of 10 V was applied to form a dielectric layer (dielectric oxide film) on the surface of the tantalum sintered compact, thereby obtaining a capacitor element.

[0081] The capacitor element was immersed in the oxidant / dopant solution, removed, and dried at 105°C for 10 minutes. The dried capacitor element was immersed in an ethanol solution of EDOT with a concentration of 35% by mass, removed after 1 minute, and then chemical oxidative polymerization was performed for 2 hours in an atmosphere of 25°C and 60% relative humidity to form a conductive polymer on the dielectric layer of the capacitor element. The capacitor element was then immersed in pure water, left for 30 minutes, and then pulled out and dried at 105°C for 60 minutes. The process from immersing the capacitor element in the oxidant / dopant solution to washing and drying after polymerization was repeated a total of eight times to obtain a capacitor element having an inner layer on a dielectric layer.

[0082] (Formation of the outer layer) The ethanol solution of Preparation Example 1 was used as a pretreatment liquid, and the capacitor element having the inner layer formed thereon was immersed in the pretreatment liquid, then pulled out and dried at 50° C. for 10 minutes to perform pretreatment.

[0083] Using the pretreated capacitor element, an outer layer was formed by carrying out chemical oxidative polymerization, washing and drying in the same manner as in the formation of the inner layer, thereby forming a conductive polymer layer on the dielectric layer of the capacitor element.

[0084] The conductive polymer layer formed on the capacitor element was then covered with carbon paste and silver paste, and then packaged with an exterior material to obtain a tantalum electrolytic capacitor. The design capacitance of the tantalum electrolytic capacitor of Example 1 was 120 μF (this also applies to the tantalum electrolytic capacitors of each of the Examples and Comparative Examples described below).

[0085] The thickness of the conductive polymer layer formed on the capacitor element by the same method as that used for producing the tantalum electrolytic capacitor was 10 μm. The thickness of the conductive polymer layer was measured as follows. The capacitor element on which the conductive polymer layer was formed was sealed with resin before being enclosed in an exterior material, and polished with a file until the surface of the capacitor element was exposed. The surface of the element was observed from the exposed direction using an optical microscope, and the thickness of the conductive polymer layer on the corner between the upper surface (the surface from which the lead wire protrudes) and the side surface of the capacitor element was measured at two points. Five samples were measured under the same conditions, and the average value of these measured values ​​rounded off to the nearest whole number was taken as the thickness of the conductive polymer layer at the end of the capacitor element (the same applies to each of the examples and comparative examples described below).

[0086] Example 2 A tantalum electrolytic capacitor was produced in the same manner as in Example 1, except that the pretreatment liquid used in forming the outer layer was changed to the ethanol solution of Preparation Example 2. The conductive polymer layer formed on the capacitor element used in this tantalum electrolytic capacitor had a thickness of 10 μm.

[0087] Example 3 A tantalum electrolytic capacitor was produced in the same manner as in Example 1, except that the pretreatment liquid used in forming the outer layer was changed to the ethanol solution of Preparation Example 3. The conductive polymer layer formed on the capacitor element used in this tantalum electrolytic capacitor had a thickness of 12 μm.

[0088] Example 4 A tantalum electrolytic capacitor was produced in the same manner as in Example 1, except that the pretreatment liquid used in forming the outer layer was changed to the ethanol solution of Preparation Example 4. The conductive polymer layer formed on the capacitor element used in this tantalum electrolytic capacitor had a thickness of 11 μm.

[0089] Example 5 A tantalum electrolytic capacitor was produced in the same manner as in Example 1, except that the pretreatment liquid used in forming the outer layer was changed to the ethanol solution of Preparation Example 5. The conductive polymer layer formed on the capacitor element used in this tantalum electrolytic capacitor had a thickness of 10 μm.

[0090] Example 6 A tantalum electrolytic capacitor was produced in the same manner as in Example 1, except that the pretreatment liquid used in forming the outer layer was changed to the ethanol solution of Preparation Example 6. The conductive polymer layer formed on the capacitor element used in this tantalum electrolytic capacitor had a thickness of 9 μm.

[0091] Example 7 A tantalum electrolytic capacitor was produced in the same manner as in Example 1, except that the pretreatment liquid used in forming the outer layer was changed to the ethanol solution of Preparation Example 7. The conductive polymer layer formed on the capacitor element used in this tantalum electrolytic capacitor had a thickness of 9 μm.

[0092] Example 8 A tantalum electrolytic capacitor was produced in the same manner as in Example 1, except that the pretreatment liquid used in forming the outer layer was changed to the ethanol solution of Preparation Example 8. The conductive polymer layer formed on the capacitor element used in this tantalum electrolytic capacitor had a thickness of 9 μm.

[0093] Example 9 A tantalum electrolytic capacitor was produced in the same manner as in Example 1, except that the pretreatment liquid used in forming the outer layer was changed to the ethanol solution of Preparation Example 9. The conductive polymer layer formed on the capacitor element used in this tantalum electrolytic capacitor had a thickness of 11 μm.

[0094] Example 10 The ethanol solution of Preparation Example 2 and the ethanol solution of Preparation Example 10 were mixed in a mass ratio of 2:1 to prepare a pretreatment liquid having a total concentration of naphthalenesulfonic acid and hydroxybenzoic acid of 30 mass %. Then, except for using this pretreatment liquid, a tantalum electrolytic capacitor was produced in the same manner as in Example 1. The conductive polymer layer formed on the capacitor element used in this tantalum electrolytic capacitor had a thickness of 10 μm.

[0095] Example 11 The ethanol solution of Preparation Example 2 and the ethanol solution of Preparation Example 10 were mixed in a mass ratio of 1:1 to prepare a pretreatment liquid having a total concentration of naphthalenesulfonic acid and hydroxybenzoic acid of 30 mass %. Then, except for using this pretreatment liquid, a tantalum electrolytic capacitor was produced in the same manner as in Example 1. The conductive polymer layer formed on the capacitor element used in this tantalum electrolytic capacitor had a thickness of 11 μm.

[0096] Example 12 The ethanol solution of Preparation Example 2 and the ethanol solution of Preparation Example 10 were mixed in a mass ratio of 1:2 to prepare a pretreatment liquid having a total concentration of naphthalenesulfonic acid and hydroxybenzoic acid of 30 mass %. Then, except for using this pretreatment liquid, a tantalum electrolytic capacitor was produced in the same manner as in Example 1. The conductive polymer layer formed on the capacitor element used in this tantalum electrolytic capacitor had a thickness of 11 μm.

[0097] Example 13 The ethanol solution of Preparation Example 2 and the ethanol solution of Preparation Example 11 were mixed in a mass ratio of 1:1 to prepare a pretreatment liquid containing naphthalenesulfonic acid, a salt of hydroxybenzoic acid, and diethanolamine at a total concentration of 30 mass%. A tantalum electrolytic capacitor was then produced in the same manner as in Example 1, except that this pretreatment liquid was used. The conductive polymer layer formed on the capacitor element used in this tantalum electrolytic capacitor had a thickness of 9 μm.

[0098] Example 14 The ethanol solution of Preparation Example 2 and the ethanol solution of Preparation Example 12 were mixed in a mass ratio of 1:1 to prepare a pretreatment liquid having a total concentration of naphthalenesulfonic acid and phthalic acid of 30 mass %. A tantalum electrolytic capacitor was then produced in the same manner as in Example 1, except for using this pretreatment liquid. The conductive polymer layer formed on the capacitor element used in this tantalum electrolytic capacitor had a thickness of 10 μm.

[0099] Comparative Example 1 A tantalum electrolytic capacitor was produced in the same manner as in Example 1, except that no pretreatment was performed when the outer layer was formed.

[0100] Comparative Example 2 A tantalum electrolytic capacitor was produced in the same manner as in Example 1, except that the pretreatment liquid used in forming the outer layer was changed to the ethanol solution of Preparation Example 12.

[0101] Comparative Example 3 A tantalum electrolytic capacitor was produced in the same manner as in Example 1, except that the pretreatment liquid used in forming the outer layer was changed to the ethanol solution of Preparation Example 13.

[0102] Comparative Example 4 A tantalum electrolytic capacitor was produced in the same manner as in Example 1, except that the pretreatment liquid used in forming the outer layer was changed to the ethanol solution of Preparation Example 14.

[0103] Comparative Example 5 A tantalum electrolytic capacitor was produced in the same manner as in Example 2, except that the pretreatment liquid was also used when forming the inner layer, according to the procedure described below.

[0104] The capacitor element on which the dielectric layer (dielectric oxide film) was formed was immersed in the ethanol solution of Preparation Example 2, then pulled out, and dried at 50°C for 10 minutes to perform pretreatment. The pretreated capacitor element was immersed in the above oxidant / dopant solution, then pulled out, and dried at 105°C for 10 minutes. The dried capacitor element was immersed in an ethanol solution of EDOT with a concentration of 35% by mass, and after 1 minute, it was taken out, and then chemical oxidation polymerization was performed for 2 hours in an atmosphere of a temperature of 25°C and a relative humidity of 60%, to form a conductive polymer on the dielectric layer of the capacitor element. Next, this capacitor element was immersed in pure water, left for 30 minutes, then pulled out, and dried at 105°C for 60 minutes. The process of immersing the capacitor element in the pretreatment solution, immersing in the oxidant / dopant solution, washing after polymerization, and drying were repeated a total of 8 times to obtain a capacitor element having an inner layer on the dielectric layer.

[0105] The tantalum electrolytic capacitors produced in the examples and comparative examples were evaluated as follows.

[0106] <Initial characteristic evaluation> [Capacitance (CAP) measurement] Ten tantalum electrolytic capacitors from each of the examples and comparative examples were measured at 25°C and 120 Hz using an LCR meter (4284A) manufactured by Hewlett Packard, and the average value of the ten measured values ​​was calculated for each of the examples and comparative examples.

[0107] [Equivalent series resistance (ESR) measurement] The ESR of ten tantalum electrolytic capacitors of each of the Examples and Comparative Examples was measured at 100 kHz under conditions of 25°C using an LCR meter (4284A) manufactured by Hewlett Packard, and the average value of the ten measured values ​​was calculated for each of the Examples and Comparative Examples.

[0108] <Heat resistance evaluation> Ten tantalum electrolytic capacitors each from the Examples and Comparative Examples were stored in an environment of 150°C for 400 hours, and then the CAP and ESR were measured in the same manner as above. For each of the Examples and Comparative Examples, the average of the ten measured values ​​was calculated by rounding off to the first decimal place. The rate of change of the CAP was calculated according to the following formula, and the rate of change of the ESR was calculated (times) by dividing the obtained value by the average ESR value at the time of the initial characteristic evaluation.

[0109] Percentage change in CAP heat resistance evaluation measurements from initial characteristic evaluation measurements: Change rate (%) = 100 × (heat resistance evaluation measurement value ÷ initial characteristic evaluation measurement value)

[0110] For the electrolytic capacitors produced in the Examples and Comparative Examples, the compositions of the pretreatment liquids used in forming the outer layers are shown in Tables 2 and 3, and the above evaluation results are shown in Table 4. In Table 2, when the ethanol solution prepared in any one of Preparation Examples 1 to 14 was used alone as the pretreatment liquid, this is shown in the column "Component-1", and when any two of the ethanol solutions prepared in Preparation Examples 1 to 14 were mixed and used as the pretreatment liquid, the ethanol solutions used are shown in the columns "Component-1" and "Component-2", and the mixing ratio thereof is shown in the column "Mixing ratio".

[0111] [Table 2]

[0112] [Table 3]

[0113] [Table 4]

[0114] As shown in Table 4, the electrolytic capacitors of Examples 1 to 14, which were fabricated by forming an inner layer of a conductive polymer on the dielectric layer of a capacitor element, performing pretreatment using a pretreatment liquid containing an aromatic sulfonic acid or a salt other than its transition metal salt and having an appropriate concentration of an organic acid having an aromatic ring or a salt other than its transition metal salt, and then forming an outer layer of a conductive polymer, had a lower initial ESR and smaller changes in CAP and ESR during heat resistance evaluation than the electrolytic capacitor of Comparative Example 1, which was fabricated without treatment with a pretreatment liquid, and thus had excellent heat resistance.

[0115] On the other hand, the electrolytic capacitor of Comparative Example 2, which was prepared using a pretreatment solution containing only aromatic carboxylic acid without using any salt other than aromatic sulfonic acid or its transition metal salt, had a higher initial ESR than the electrolytic capacitor of the Example. In addition, the electrolytic capacitor of Comparative Example 3, which was prepared using a pretreatment solution containing aromatic sulfonic acid or its salt other than its transition metal salt but with a too low concentration of organic acid having an aromatic ring or its salt other than its transition metal salt, did not obtain the effect of pretreatment, had a high initial ESR, and the changes in CAP and ESR during heat resistance evaluation were large. In addition, the electrolytic capacitor of Comparative Example 4, which was prepared using a pretreatment solution containing aromatic sulfonic acid or its salt other than its transition metal salt but with a too high concentration of organic acid having an aromatic ring or its salt other than its transition metal salt, had a high initial ESR. Furthermore, the electrolytic capacitor of Comparative Example 5, which was prepared using a pretreatment solution for forming the inner layer, had significantly inferior initial characteristics and heat resistance.

Claims

1. A method for producing an electrolytic capacitor including a capacitor element having a dielectric layer formed on a metal porous body, the capacitor element having a conductive polymer layer on the dielectric layer, the method comprising the steps of: The step of forming the conductive polymer layer comprises: an inner layer forming step of forming an inner layer of a conductive polymer layer by carrying out one or more operations of chemically oxidizing and polymerizing thiophene or a derivative thereof on a surface of the dielectric layer using aromatic ferric sulfonate as an oxidizing agent and dopant; a step of applying a pretreatment liquid to the capacitor element on which the conductive polymer inner layer has been formed and drying the pretreatment liquid, and performing an operation of chemically oxidizing and polymerizing thiophene or a derivative thereof using aromatic ferric sulfonate as an oxidizing agent and dopant on the pretreated capacitor element one or more times to form a conductive polymer outer layer on the inner layer, The method for manufacturing an electrolytic capacitor is characterized in that the pretreatment liquid contains an aromatic ring-containing organic acid or a salt thereof other than a transition metal salt thereof at a concentration of 10 to 50 mass %, and the organic acid or the salt thereof contains at least an aromatic sulfonic acid or a salt thereof other than a transition metal salt thereof.

2. 2. The method for producing an electrolytic capacitor according to claim 1, wherein the pretreatment liquid further contains, as the organic acid containing an aromatic ring or a salt thereof other than the transition metal salt thereof, an aromatic carboxylic acid or a salt thereof other than the transition metal salt thereof.

3. 2. The method for producing an electrolytic capacitor according to claim 1, wherein the aromatic sulfonic acid or a salt thereof other than a transition metal salt thereof has a naphthalene skeleton or a benzene skeleton and contains a carboxyl group.

Citation Information

Patent Citations

  • Method for manufacturing electrolytic capacitor

    JP2020178107A

  • Conductive polymer and solid electrolytic capacitor using same

    WO2005014692A1